Rancang Bangun Aplikasi Berbagi Berbasis Lokasi Menggunakan Quick Response Code dan Metode Geolocation - Danry Ray; Dodick Zulaimi Sudirman; Yunita Riris Widawaty (Ultimatics : Jurnal Teknik Informatika, 2014)
As more sophisticated the technology, it will give a harder challenge for the libraries to fulfill their patrons requirement. For the sake of a great technology experience, library of Universitas Multimedia Nusantara is trying to adopt QR Code technology and geolocation method into it’s system. User who has a QR Code to be scanned will share their activities, such as read and borrow. Users can also do a check-in if they do not want to scan a QR Code. After dealing with QR Code, the application will provide users with the location where a QR Code was scanned. A variety of a scan distance will impact to the variety of the point or reward those users can achieve. There are also several things to be done that could enhanced the accuracy of the location finder, like comparing the result between GPS provider and Network provider based on certain variable (time and accuracy) and displaying both the results to the user so they can choose their own preference because of some factors that could cause an inconsistency while finding location is executed like mobile signal, amount of cell tower, and location of user. Index Terms - QR Code, geolocation, sharing system, library of Universitas Multimedia Nusantara